Characterization and utilization of rice, legume and rape straws - Abreu J.M.F.; Bruno-Soares A.M. (Exploitation of Mediterranean roughage and by-products, 1998)
Legume (9 species), rice (3 varieties) and rape straws were given to 6-8 rams in metabolic cages, together with several levels of energy and protein supplementation. Three of the legume straws and all three rice straws were also studied in rumen cannulated sheep. Determinations of chemical composition (ash, CP, NDF, ADF, ADL, some minerals), organic matter digestibility (OMD), metabolizable energy (ME) and voluntary intake of the feeds were made; rumen degradability of organic matter was also assessed with the nylon bag technique. Legume straws had 4.2-10.6 per cent CP, 58.0-82.4 per cent NDF. Rice and rape straws had approximately 4 per cent CP, 77 per cent NDF. OMD varied between 43.5 per cent and 55.3 per cent in legume straws, between 47.0 per cent and 51.9 per cent in rice straws. Rape straw OMD was about 40 per cent. Voluntary intakes varied between 48 g and 77 g per kg LW0.75 in legume straws, they were around 50 g per kg LW0.75 in rice straws and 30 g per kg LW0.75 in rape straw. Organic matter degradability was highest, 68.5 per cent, in rice straw (cv. Ringo), lowest in horse bean straw, 53.9 per cent.